PENGARUH FINANCIAL ATTITUDE DAN FINANCIAL KNOWLEDGE TERHADAP KEPUTUSAN KEUANGAN PADA PEMILIK USAHA KECIL DAN MENENGAH (UKM) DI PULAU LOMBOK: SUATU PERSPEKTIF BEHAVIORAL FINANCE - Siti Aisyah Hidayati; Sri Wahyulina; Embun Suryani (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2020)
This study aims to analyze the effect of Financial Attitude and Financial Knowledge on financial decisions on Small and Medium Business Owners (UKM) on Lombok Island. The theoretical contribution of this research is expected to contribute to science and the development of behavioral finance theories related to financial decision making in Small and Medium Enterprises (SMEs). It is also expected that behavioral finance will be the subject of financial management courses. Furthermore, the practical contribution of this research is expected to provide input, suggestions and recommendations to the policy maker of the NTB Provincial Government in making policies related to the development of SMEs. This research is a quantitative approach based research, with the type of explanatory research. The study population is all SMEs in the island of Lombok. The sampling technique is done by using Non probability sampling, which uses judgment sampling, which is choosing SMEs that are engaged in the pottery industry and have already exported. From the existing population, there are 35 (thirty-five) SMEs that can be taken as samples. Respondents in this study are the owners of each of these UKM. Data collection techniques used in this study were using a questionnaire. To achieve research objectives and hypothesis testing, the data obtained will be processed according to needs using GSCA (Generalized Structured Component Analysis) statistical tools. The results showed that Financial Attitudes had a positive and significant effect on financial decision making by SME owners and owners. This means that the better the Financial Attitudes owned by SME owners, the bolder they are in making financial decisions. Financial Knowledge has a positive and significant impact on financial decision making by SME owners and owners. This means that the better the Financial Knowledge possessed by SME owners, the bolder the financial decisions will be.